Bond strength of fibre-reinforced polymer bars in engineered cementitious composites. Issue 1 (26th September 2017) - Hossain, Khandaker M. A.; Alam, Shah; Anwar, Muhammed S.; Julkarnine, Khandaker M. Y.
Abstract : The high strain capacity while maintaining small crack width makes flowable fibre-reinforced engineered cementitious composites (ECCs) an ideal durable material for construction. ECCs reinforced with glass-f ibre-reinforced polymer (GFRP) bars is an emerging technology. The full understanding of the bond characteristics of GFRP bars in ECCs is important for this new technology to be adopted in bridge/building constructions. Experimental investigations accompanied by code-based theoretical investigations were conducted to evaluate the bond behaviour of GFRP bars embedded in normal concrete (NC) and ECCs. Ninety pullout specimens were tested. The test variables were GFRP bar types (low modulus (LM) and high modulus (HM)), diameter of the bar (12·7, 15·9 and 19·1 mm) and embedded length (5, 7 and 10 times bar diameter). The bond strengths of both LM and HM bars embedded in the ECC were found to be higher than of those embedded in NC. This confirmed the superior bond characteristics of ECC compared with NC. Bond strength predictions based on CSA S6-06 and CSA S806-12 were found to be conservative while predictions based on ACI 440.1R-06 were found to be unconservative for the majority of specimens. Existing code-based equations need to be modified for the calculation of the bond strength of GFRP bars in ECCs.